Cost-effectiveness of a fracture liaison service—a real-world evaluation after 6 years of service provision. Issue 1 (January 2016) - Yong, J.; Masucci, L.; Hoch, J.; Sujic, R.; Beaton, D.
Abstract Summary The cost-effectiveness of a less intensive fracture liaison service is unknown. We evaluated a fracture liaison service that had been educating and referring patients for secondary prevention of osteoporotic fractures for 6 years. Our results suggest that a less intensive fracture liaison service, with moderate effectiveness, can still be worthwhile. Introduction Fragility fractures are common among older patients; the risk of re-fracture is high but could be reduced with treatments; different versions of fracture liaison service have emerged to reduce recurrent osteoporotic fractures. But the cost-effectiveness of a less intensive model is unknown. The objective of this study was to assess the cost-effectiveness of the Ontario Fracture Clinic Screening program, a fracture liaison service that had been educating and referring fragility fracture patients across Ontario, Canada to receive bone mineral density testing and osteoporosis treatments since 2007. Methods We developed a Markov model to assess the cost-effectiveness of the program over the patients' remaining lifetime, using rates of bone mineral density testing and osteoporosis treatment and cost of intervention from the program, and supplemented it with the published literature. The analysis took the perspective of a third-party health-care payer. Costs and benefits were discounted at 5 % per year. Sensitivity analyses assessed the effects of different assumptions on the results. Results The program improved quality-adjusted life-years (QALYs) by 4.3 years and led to increased costs of CAD 83, 000 for every 1000 patients screened, at a cost of 19, 132 per QALY gained. The enhanced model, the Bone Mineral Density (BMD) Fast Track program that includes ordering bone mineral density testing, was even more cost-effective (5720 per QALY gained). Conclusions The Ontario Fracture Clinic Screening program appears to be a cost-effective way to reduce recurrent osteoporotic fractures.